2019
DOI: 10.1017/s0950268819000426
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and genotypic characterisation of dissemination patterns of uropathogenicEscherichia coliin a community

Abstract: To characterise the dissemination patterns of uropathogenic Escherichia coli (UPEC) in a community, we conducted a study utilising molecular and fundamental descriptive epidemiology. The subjects, consisted of women having community-acquired acute urinary tract infection (UTI), were enrolled in the study from 2011 to 2012. UPEC isolates were subjected to antibacterial-susceptibility testing, O serogrouping, phylotyping, multilocus-sequence typing with phylogenetic-tree analysis and pulsed-field-gel electrophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…However, the distinction in virulence between hospital-associated and community-acquired strains is not as unequivocal as with MRSA and MDR K. pneumoniae because in contrast to these agents CA-E. coli strains, as primarily urogenital pathogens, are often exposed to fluoroquinolones and other antibiotics impacting the fitness of the isolates in a clonedependent fashion. This is the reason why in contrast to MRSA and MDR K. pneumonaiae the fluoroquinolone-selected clone of MDR E. coli, ST131, may feature prominently in communityacquired infections (Blanco et al, 2013;Doi et al, 2013;Nicolas-Chanoine et al, 2014;Chong et al, 2018;Jamborova et al, 2018;Matsukawa et al, 2019).…”
Section: The Virulence Component In Mdr E Colimentioning
confidence: 99%
“…However, the distinction in virulence between hospital-associated and community-acquired strains is not as unequivocal as with MRSA and MDR K. pneumoniae because in contrast to these agents CA-E. coli strains, as primarily urogenital pathogens, are often exposed to fluoroquinolones and other antibiotics impacting the fitness of the isolates in a clonedependent fashion. This is the reason why in contrast to MRSA and MDR K. pneumonaiae the fluoroquinolone-selected clone of MDR E. coli, ST131, may feature prominently in communityacquired infections (Blanco et al, 2013;Doi et al, 2013;Nicolas-Chanoine et al, 2014;Chong et al, 2018;Jamborova et al, 2018;Matsukawa et al, 2019).…”
Section: The Virulence Component In Mdr E Colimentioning
confidence: 99%
“…In another study carried out in UPEC strains (n=167), the most frequent ST identified was ST131 (n=20), mainly corresponding to phylogenetic group B2, which also includes ST ST-1193, ST-14, ST-10 and ST-69, found in the present study (Table 1). 47 In this study, group O25:H4-ST-131, belonging to phylogenetic group B2 of E. coli was the most prevalent group in the patients studied. Therefore, it is important to establish epidemiological monitoring programs in the region, focused specifically on controlling bacterial resistance to antimicrobials.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, we tested for synergistic activity using checkerboard assays against antibiotic-sensitive E. coli strains as the major causative agent for uncomplicated cystitis. Strains were selected according to their sequence types to represent four of the most prevalent sequence types of cystitis causing E. coli —131 ( E. coli CHD94), 95 ( E. coli UTI89), 73 ( E. coli CHD3), and 69 ( E. coli CHD22) [ 14 ]. The combination of thyme and tea tree resulted in an additive 8-fold reduction of the MIC and MBC values of both essential oils compared to the substances alone ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%